Clinical-constitutional features in patients with vegetative dysfunction and emotional disturbance - N. G. Voropai; O. B. Doronina (Бюллетень сибирской медицины)
Аutonomic dysfunction and psychic tension have both and several properties. Anthropometric measurements, research of vegetative tone and vegetative reactivity, research of neurological status were conducted.